Shakespeare's Representation of Weather, Climate and Environment The Early Modern 'Fated Sky' - Chiari, Sophie (Edinburgh University Press, 2018)
This monograph explores the importance of weather and changing skies in early modern England while acknowledging the fact that traditional representations and religious beliefs still fashioned people's relations to meteorological phenomena.